2020
DOI: 10.3133/sir20205089
|View full text |Cite
|
Sign up to set email alerts
|

Status of groundwater-level altitudes and long-term groundwater-level changes in the Chicot, Evangeline, and Jasper aquifers, Houston-Galveston region, Texas, 2020

Abstract: For an overview of USGS information products, including maps, imagery, and publications, visit https://store.usgs.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…The following overview of the geology and hydrogeology of the study area is modified from Kasmarek and Ramage (2017) and Braun and Ramage (2020). The Gulf Coast aquifer system hydrogeologic units include the Chicot aquifer, the Evangeline aquifer, the Burkeville confining unit, the Jasper aquifer, and the Catahoula confining unit (figs.…”
Section: Geology and Hydrogeology Of The Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…The following overview of the geology and hydrogeology of the study area is modified from Kasmarek and Ramage (2017) and Braun and Ramage (2020). The Gulf Coast aquifer system hydrogeologic units include the Chicot aquifer, the Evangeline aquifer, the Burkeville confining unit, the Jasper aquifer, and the Catahoula confining unit (figs.…”
Section: Geology and Hydrogeology Of The Study Areamentioning
confidence: 99%
“…Because of this hydraulic connection, water-level changes (changes in the depth to water in feet below land surface) that occur in one aquifer can affect water levels in the adjoining aquifer (Kasmarek and others, 2010). Supporting evidence of the interaction of groundwater flow between the Chicot and Evangeline aquifers includes maps of long-term water-level changes that show areas where rises and declines are approximately spatially coincident and colocated wells with different screened-interval depths where rises or declines in water levels are approximately coincident in time (for example, Braun and others, 2019;Braun and Ramage, 2020). Additional evidence of the hydraulic connection between the Chicot and Evangeline aquifers is provided by Borrok and Broussard (2016, p. 330); their geochemical evaluation of the Chicot aquifer system from 1993 to 2015 in Louisiana indicated that in some years (1998, 2008, and 2011) certain wells screened in the Chicot aquifer "appeared to be tapping water with a geochemistry (temperature, salinity, alkalinity, [and so forth]) matching the underlying Evangeline aquifer."…”
Section: Geology and Hydrogeology Of The Study Areamentioning
confidence: 99%
See 3 more Smart Citations